Athenry Dominican Priory, south nave wall, niche, base - O'Donovan, Danielle (My University, 2008)
Base of middle niche in south wall of nave. Moulding is broken, but what remains, from top down, comprises: water-holding element, roll with two fillets, chamfer, plinth.
Niche
Keywords: water-holding; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Late Medieval; roll-and-fillet moldings; moldings, hollow; plinth